Influence of Stress Field Changes on Eruption Initiation and Dynamics: A Review - Sulpizio, Roberto; Massaro, Silvia (Frontiers in Earth Science, 2017)
Three main (first-order) mechanisms of stress variation able to influence the triggering of volcanic eruptions and the possible impact on eruption dynamics were reviewed. They are short- and long-term unloading, seismic energy effects, and changes in far field stress due to geodynamic processes. An equilibrium equation for rupture of magma chamber and opening of a dyke up to the surface was derived, taking into account the contribution of each mechanism within the equation. The equation considers the effect of possible superimposition of the three mechanisms with internal processes to the magmatic system, and it was also used for discussing the possible influence on eruption dynamics. The different possible contribution to the eruption triggering was discussed for each mechanism, highlighting how, in many cases, a single mechanism alone is not sufficient for driving eruptive activity if the magmatic system is not close to eruptive conditions.